2021
DOI: 10.2196/24497
|View full text |Cite
|
Sign up to set email alerts
|

Medical Morphology Training Using the Xuexi Tong Platform During the COVID-19 Pandemic: Development and Validation of a Web-Based Teaching Approach

Abstract: Background Histology and Embryology and Pathology are two important basic medical morphology courses for studying human histological structures under healthy and pathological conditions, respectively. There is a natural succession between the two courses. At the beginning of 2020, the COVID-19 pandemic suddenly swept the world. During this unusual period, to ensure that medical students would understand and master basic medical knowledge and to lay a solid foundation for future medical bridge cours… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The overall rating score is 4.65 out of 5 1 Khalaf et al (2020) [ 74 ] OL; UG dental students at University of Sharjah Online questionnaire Traditional learning ( N = 65) Cross-sectional study Students were very satisfied with the online exam. Students with online exam experience were more satisfied with OL than students who lack experience with online exam ( p < 0.05) 1 Khan et al (2021) [ 21 ] OL; UG medical students from North India Online questionnaire Traditional learning ( N = 103) Mixed study 62%-80%, showed satisfaction toward OL 1 Kim et al (2020) [ 48 ] OL; UG medical students from Seoul National University Online questionnaire Traditional learning ( N = 456) Cross-sectional study 62.2% of the students were satisfied with OL compared to f2f learning 1 Liu et al (2021) [ 75 ] OL; UG medical students from Shandong First Medical University Online questionnaire Traditional learning ( N = 512) Cross-sectional study 71.3% of the Histology and Embryology students and 82.5% and Pathology students were very satisfied with OL. Only 37% want to return to traditional teaching from Pathology course while 52.1% from Histology and Embryology 1 Menon et al (2021) [ 51 ] OL; UG medical students from college hospital in South India Online questionnaire Traditional learning ( N = 370) Cross-sectional study most students were satisfied with the OL (31% scored high satisfaction, 53.6% scored moderate satisfaction), while only 15.4% were not satisfied 1 Muflih et al (2021) [ 53 ] ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall rating score is 4.65 out of 5 1 Khalaf et al (2020) [ 74 ] OL; UG dental students at University of Sharjah Online questionnaire Traditional learning ( N = 65) Cross-sectional study Students were very satisfied with the online exam. Students with online exam experience were more satisfied with OL than students who lack experience with online exam ( p < 0.05) 1 Khan et al (2021) [ 21 ] OL; UG medical students from North India Online questionnaire Traditional learning ( N = 103) Mixed study 62%-80%, showed satisfaction toward OL 1 Kim et al (2020) [ 48 ] OL; UG medical students from Seoul National University Online questionnaire Traditional learning ( N = 456) Cross-sectional study 62.2% of the students were satisfied with OL compared to f2f learning 1 Liu et al (2021) [ 75 ] OL; UG medical students from Shandong First Medical University Online questionnaire Traditional learning ( N = 512) Cross-sectional study 71.3% of the Histology and Embryology students and 82.5% and Pathology students were very satisfied with OL. Only 37% want to return to traditional teaching from Pathology course while 52.1% from Histology and Embryology 1 Menon et al (2021) [ 51 ] OL; UG medical students from college hospital in South India Online questionnaire Traditional learning ( N = 370) Cross-sectional study most students were satisfied with the OL (31% scored high satisfaction, 53.6% scored moderate satisfaction), while only 15.4% were not satisfied 1 Muflih et al (2021) [ 53 ] ...…”
Section: Resultsmentioning
confidence: 99%
“…A cross-continent comparison of the level of satisfaction was also conducted. From the 13 studies that reported higher satisfaction with the use of online learning approach, six were from Asia [ 26 , 51 , 56 , 62 , 74 , 75 ], five were from Europe [ 32 , 41 , 47 , 66 ], one from America [ 77 ], and one from Africa [ 73 ]. Meanwhile, five studies from Asia [ 43 , 58 , 61 , 65 , 68 ] and one study from Africa [ 35 ] revealed that students were not satisfied with online learning.…”
Section: Resultsmentioning
confidence: 99%
“…Although in a remote model of the practical classes tutors should understand that the preparation of the students is important in the dynamic development of the study course (Reguera & Lopez, 2021). Tutors should consider students as the main persons in the practical classes while the tutors themselves play the leading role in the process of "teach by learning and research by teaching" (Liu et al, 2021). In face of the necessity to undertake online teaching, our tutors at all levels have had to undertake novel work for the use and creation of the digital images of the skull bones.…”
Section: Discussionmentioning
confidence: 99%
“…Accessibility to the slide images outside classroom [35,44,[47][48][49][52][53][54]59,64,67], ability to annotate slides [20,35] and availability of ample free resources led to a more efficient and feasible method of learning [20,34,40,41,44,48,54,67].…”
Section: Vm Podcastmentioning
confidence: 99%
“…An overall positive acceptance for VM with a higher student satisfaction for VMbased teaching in addition to increased levels of subject interest was another reported advantage [20,22,[35][36][37]39,41,47,49,50,[53][54][55]59,60,64,66,67].…”
Section: Vm Podcastmentioning
confidence: 99%